Pesantren Vis a Vis Global Challenges, Strengthening Vision of Pesantren - In’ami, Moh; Thohir, Lalu; Sholehudin, Sholehudin (Program Studi Pendidikan Agama Islam, 2020)
The purpose of this study is to determine the challenges of pesantren during global currents; to find out the aspects that strengthen the continuity of the pesantren; and to find strategies for dealing with global challenges. The approach used in this research is qualitative with library research. The data were collected through references related to central themes. To analyze the data, several techniques were conducted such as data reduction, data presentation, and verification. The results showed that 1). The challenges of Islamic boarding schools during global currents can be in the form of thought, culture, science, and technology, as well as competition in various fields; 2). Aspects that strengthen the continuity of the pesantren to traditions and culture which are steadfastly and istiqamah fought for and preserved; 3). The pesantren's strategy in facing global challenges is to sort out every global progress by taking what is useful and removing what is harmful. Education in this Muslim-majority country has large and important role in the whole Indonesia human development. The existence of education is the pillar of science and knowledge building that is able to lead society towards development and progress. The development and progress are born and appear in the middle of people's life becomes a necessity. Occurrences that simply cannot be expected when people underestimate and ignore education. The presence of pesantren as a representation of Islamic educational institutions cannot be circumvented. Pesantren, in the Indonesian dictionary, is an indigenous Islamic institution. But over time, tough challenges began to appear.